Influência do corte da parte terminal da raquis do cacho da bananeira cv. "Prata" (Musa sp) sobre a produção total, número de pencas por cacho, comprimento e diâmetro do fruto - Moreira de Souza, Milton; Andersen , Otto; Manica, Ivo (Revista Ceres, 2025)
The present study was conducted in order to compare methods of removal male bud in banana after flowering. "Prata" banana (Musa sp.) was used in the experiment. The male bud was remove at 30 and 60 days after flowering and together with the check treatment (without removal of the male bud) were equivalent in terms of weight, number of hands and number of fruits in the bunch. This experiment revealed no differences also for harvest time, length and diameter of the fruits in the first andlast hands.